COMMUTING IN THE WARSAW SUBURBAN AREA FROM A SPATIAL PERSPECTIVE - AN EXAMPLE OF EMPIRICAL RESEARCH - Drejerska, Nina; Chrzanowska, Mariola (Acta Universitatis Lodziensis. Folia Oeconomica, 2015)
Commuting plays a significant role in forming metropolitan areas. It is one of the basic criteria for delineation of functional areas, including metropolitan regions. The objectives of this study included determining the Warsaw labour market and examining the influence of some spatial patterns on the intensity of commuting to Warsaw in the investigated communes. The research was conducted in a form of questionnaire interviews in 800 households from 30 communes of the Warsaw suburban zone, involving 2 215 adult participants. The analysis was based on a binary matrix B and weight matrix W standardised according to rows. A criterion of a common border was assumed as a neighbouring criterion. The weight matrix was built in the first step, then the global Moran’s statistic was calculated for each workplace localisation. Then local Moran’s statistics were calculated. The global Moran’s statistic was significant only for respondents commuting to another village. There were clusters of communes with a similar proportion of respondents commuting to another village, usually inhabitants of smaller villages commuting to the communal centre for work in public services or retail. As far as local Moran’s statistics are concerned, they allowed the pointing out of some examples of communes surrounded by similar or different commuting patterns. A spatial structure of commuting does not facilitate analysis. As a result, the relationships form radial patterns with Warsaw as the centre, rather than clusters.